(untitled) (Research, Society and Development, 2021)
The quality of the electromechanical maintenance service applied at the Basic Sanitation Company of Piauí, in the interior board, is still quite deficient and needs to be adjusted in its processes. It is action research in which the researcher has an active role in the decision process. In this study, the quality of electromechanical maintenance applied in the company was evaluated. Interviews were carried out with specific questionnaires with the company’s employees and customers. Paraconsistent logic was used to assess the quality of maintenance applied in the process. With the results found, it was observed that corrective maintenance is not the most adequate, and suggestions for changes in the process and the style of quality management are presented to promote regularity, service improvement, and organizational development of the company.